A thousand beginnings and endings : 15 retellings of Asian myths and legends - Oh, Ellen; Chapman, Elsie; Chokshi, Roshani; Wong, Alyssa; Lee, Lori M.; Charaipotra, Sona; Bodard, Aliette de; Myers, E. C. (Eugene C.), 1978-; Saeed, Aisha; Chhibber, Preeti; Ahdieh, Renée; Kanakia, Naomi; et al. (Greenwillow Books, an imprint of HarperCollinsPublishers, 2018)
Fifteen authors of Asian descent reimagine the folklore and mythology of East and South Asia, in short stories ranging from fantasy to science fiction to contemporary, from romance to tales of revenge.